COVID-19 in Germany and China: mitigation versus elimination strategy - Guangyu Lu; Oliver Razum; Albrecht Jahn; Yuying Zhang; Brett Sutton; Devi Sridhar; Koya Ariyoshi; Lorenz von Seidlein; Olaf Müller (Global Health Action)
Background: The COVID-19 pandemic shows variable dynamics in WHO Regions, with lowest disease burden in the Western-Pacific Region. While China has been able to rapidly eliminate transmission of SARS-CoV-2, Germany – as well as most of Europe and the Americas – is struggling with high numbers of cases and deaths. Objective: We analyse COVID-19 epidemiology and control strategies in China and in Germany, two countries which have chosen profoundly different approaches to deal with the epidemic. Methods: In this narrative review, we searched the literature from 1 December 2019, to 4 December 2020. Results: China and several neighbours (e.g. Australia, Japan, South Korea, New Zealand, Thailand) have achieved COVID-19 elimination or sustained low case numbers. This can be attributed to: (1) experience with previous coronavirus outbreaks; (2) classification of SARS-CoV-2 in the highest risk category and consequent early employment of aggressive control measures; (3) mandatory isolation of cases and contacts in institutions; (4) broad employment of modern contact tracking technology; (5) travel restrictions to prevent SARS-CoV-2 re-importation; (6) cohesive communities with varying levels of social control. Conclusions: Early implementation of intense and sustained control measures is key to achieving a near normal social and economic life.